Oxidative Stress and Gut-Derived Lipopolysaccharides in Neurodegenerative Disease: Role of NOX2 - Pigozzi, Fabio; Cacciafesta, Mauro; Violi, Francesco; Carnevale, Roberto; Wenzel, Philip; Fossati, Chiara; Spalice, Alberto; Perri, Ludovica; Nocella, Cristina; Inghilleri, Maurizio; Zicari, Anna Maria; Ettorre, Evaristo; et al. (Oxidative medicine and cellular longevity, 2020)
Background. Neurodegenerative diseases (ND) as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis represent a growing cause of disability in the developed countries. The underlying physiopathology is still unclear. Several lines of evidence suggest a role for oxidative stress and NADPH oxidase 2 (NOX2) in the neuropathological pathways that lead to ND. Furthermore, recent studies hypothesized a role for gut microbiota in the neuroinflammation; in particular, lipopolysaccharide (LPS) derived from Gram-negative bacteria in the gut is believed to play a role in causing ND by increase of oxidative stress and inflammation. The aim of this study was to assess NOX2 activity as well as serum 8-iso-prostaglandin F2α (8-iso-PGF2α), serum H2O2, and LPS in patients with ND compared to controls. Methods. One hundred and twenty-eight consecutive subjects, including 64 ND patients and 64 controls (CT) matched for age and gender, were recruited. A cross-sectional study was performed to compare serum activity of soluble NOX2-dp (sNOX2-dp), blood levels of isoprostanes, serum H2O2, and LPS in these two groups. Serum zonulin was used to assess gut permeability. Results. Compared with CT, ND patients had higher values of sNOX2-dp, 8-iso-PGF2α, H2O2, and LPS. Simple linear regression analysis showed that sNOX2-dp was significantly correlated with serum LPS (Rs=0.441; p<0.001), zonulin (Rs=0.411; p<0.001), serum H2O2 (Rs=0.329; p<0.001), and 8-iso-PGF2α (Rs=0.244; p=0.006). LPS significantly correlated with serum zonulin (Rs=0.818; p<0.001) and 8-iso-PGF2α (Rs=0.280; p=0.001). A multiple linear regression analysis was performed to define the independent predictors of sNOX2-dp. LPS (SE, 0.165; standardized coefficient β, 0.459; p<0.001) and 8-iso-PGF2α (SE, 0.018; standardized coefficient β, 0.220; p=0.005) emerged as the only independent predictive variables associated with sNOX2-dp (R2=57%). Conclusion. This study provides the first report attesting that patients with ND have high NOX2 activation that could be potentially implicated in the process of neuroinflammation.